Tarsier Goggles: a virtual reality tool for experiencing the optics of a dark-adapted primate visual system - Samuel R. Gochman; Marilyn Morano Lord; Naman Goyal; Kristie Chow; Benjamin K. Cooper; Lauren K. Gray; Stephanie X. Guo; Kylie A. Hill; Stephen K. Liao; Shiyao Peng; Hyun J. Seong; Alma Wang; et al. (Evolution: Education and Outreach, 2019)
Abstract Charles Darwin viewed eyes as the epitome of evolution by natural selection, describing them as organs of extreme perfection and complication. The visual system is therefore fertile ground for teaching fundamental concepts in optics and biology, subjects with scant representation during the rise and spread of immersive technologies in K-12 education. The visual system is an ideal topic for three-dimensional (3D) virtual reality learning environments (VRLEs), and here we describe a 3D VRLE that simulates the vision of a tarsier, a nocturnal primate that lives in southeast Asia. Tarsiers are an enduring source of fascination for having enormous eyes, both in absolute size and in proportion to the size of the animal. Our motivation for developing a tarsier-inspired VRLE, or Tarsier Goggles, is to demonstrate the optical and selective advantages of hyperenlarged eyes for nocturnal visual predation. In addition to greater visual sensitivity, users also experience reductions in visual acuity and color vision. On a philosophical level, we can never know the visual world of another organism, but advances in 3D VRLEs allow us to try in the service of experiential learning and educational outreach.